Spreading of the Conception of Natural Right in Lithuania - Nesavas, Antanas (Problemos, 1989)
In the paper the appearance and the spreading of the conception of natural right in Lithuania in the 16th and 17th centuries is considered. The economic and cultural factors promoting the spreading are pointed out. It is showed that the conception was used in various purposes. Namely, A. Volan, M. Smiglecki, and A. Olizarovius used it to criticize feudalism, while P. Skarga – in defence of feudalism.